STRATEGI PEMASARAN DI PT. MADUBARU KABUPATEN BANTUL - Agus Setyawan; Susi Widiatmi (Fakultas Pertanian UST, 2018)
This research is conducted with the aim of knowing what alternative marketing strategy is appropriate in PT. Madubaru. The resarch uses data collection techniques by interview and observation data analysis using FRED R.DAVID concept through 3 strategy formulation that is early stege using IFAS and EFAS matrix.the next step using SWOT amd IE matrix to get alternativ strategy final stage using QSPM matrix. Based on the results of IFAS and EFAS, it can be found that the total summary for IFAS is 2,5758 while for EFAS is 3,289. On the level using the SWOT matrix. There are a few alternative strategy possibilies of using strengths to seize opportunities, using opportunities to handle weaknesses using streng to avoid threat and to minimalize. Based on the internal exsternal matrix (IE) it is found that PT. Madubaru is at the level of growth and establishment. The approprirate strategy on this position is the market penetration, market development and product product development strategies. Based on the result of QSPM, the companies decision stage should employ the main alternative strategy, which is the product development strategy with the total amout of interest TAS ia 6,53.